Dr. Quinn medicine woman. The complete season three [videorecording (DVD)] - Seymour, Jane, 1951-; Allen, Chad, 1974-; Lando, Joe, 1961-; Bean, Orson (A & E Networks ; Distributed by LionsGate, 2013)
Dr. Michaela 'Mike' Quinn defies convention when she forsakes her home in genteel Boston for the rough-and-tumble life of the frontier. Features all 25 episodes from the third season, including the wedding of Dr. Mike and Sully. Bonus features include commentary, cast biographies, and more. (This title has been repackaged.).